NlugOBP1 in Nilaparvata lugens involved in the perception of repellent agent geraniol - Ke Ke; Shuai Wu; Ke Hu; Xun Liao; Ming Li; Rongyu Li (Scientific Reports)
Abstract The brown planthopper Nilaparvata lugens (Stål) is one of the most prominent rice pests. Current methods for effectively controlling N. lugens primarily involve cultivating resistant varieties or synthesizing insecticides. However, with the increasing awareness of agricultural product safety, utilizing the volatiles of essential oils has gradually become a feasible approach for the green prevention and control of pests. In this study, we determined the repellent activity of 16 plant essential oils against N. lugens. The results revealed that citronella oil exhibited the best repellent activity. Specifically, geraniol, a main component of citronella oil, exhibited excellent repellent and oviposition deterrence activities, with repellency of 91.76% at 500 µg/cm2 and oviposition deterrence of 83.95% at 2000 mg/L. Under geraniol treatment, the expression levels of NlugOBP1, NlugOBP2, NlugOBP3, NlugOBP4, and NlugOBP9 odorant-binding proteins (OBPs) in N. lugens were significantly down-regulated by 44.40%, 51.32%, 30.16%, 53.89%, and 44.26%, respectively. However, When the expression of the NlugOBP1 gene was knocked down by an RNA interference (RNAi) technique, BPH showed no preference, geraniol exerted little repellent activity. This indicates that NlugOBP1 played an important role in the perception and recognition of geraniol by N. lugens.